Injury characteristics of young elite inline speed skaters: A one season retrospective study - Quintana-Cepedal, M.; Rodríguez, M. Á.; Nuño-Iglesias, N.; Del Valle, M.; Crespo, I.; Olmedillas, H. (The Physician and Sportsmedicine, 2024)
Objectives Determining the rate of injuries related to a certain sport is accepted as the primary step toward designing, implementing and evaluating injury prevention programs. This observational and retrospective study was to examine the injuries sustained by elite young Spanish inline speed skaters during a season.